TAp73 modulates proliferation and ferroptosis in mammary epithelial cells - Sun, Wenqiang; Ren, Hanjun; Chen, Le; Zhang, Bingfei; Mei, Liping; Wen, Jiaqi; Zhang, Yilu; Li, Jiaqi; Yan, Yongping; Lai, Songjia (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTAp73, a transcriptionally active isoform of the p73 gene, is essential for epithelial tissue development. Ferroptosis, a regulated form of cell death characterized by lipid peroxidation and reactive oxygen species (ROS) accumulation, has been increasingly studied in recent years. However, its role in epithelial cells and the regulatory function of TAp73 in this context remain poorly understood.MethodsWe investigated the role of TAp73 in epithelial cell proliferation and ferroptosis using ectopic overexpression and RNA interference approaches. Cell proliferation was assessed through colony formation and DNA synthesis assays. Ferroptosis was induced using RSL3, and the effects were evaluated by measuring cell viability, ROS levels, and the expression of ferroptosis-associated genes PTGS2 and TFRC.ResultsTAp73 overexpression significantly increased p21 expression, suppressed colony formation and DNA synthesis, thereby inhibiting cell proliferation. In contrast, TAp73 knockdown reduced p21 levels and enhanced cell proliferation. RSL3 treatment induced a dose-dependent increase in cell death and ROS accumulation, confirming the susceptibility of epithelial cells to ferroptosis. Furthermore, TAp73 overexpression enhanced RSL3-induced ferroptosis by upregulating PTGS2 and TFRC, while TAp73 knockdown diminished their expression, reducing oxidative stress and lipid peroxidation.ConclusionTAp73 acts as a dual regulator of epithelial cell fate by inhibiting proliferation and promoting ferroptosis. These findings reveal a novel role for TAp73 in epithelial cell biology and suggest potential therapeutic targets for diseases involving epithelial cell death.